THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING MODEL IN ENVIRONMENT EDUCATION IN KINDERGARTEN - Djoehaeni, Heny (EDUTECH, 2016)
Abstract. This research is encouraged by environmental issues that occurred recently, so these require a full concern from various fields, including the education field. Environmental education taught from early age will foster young learner's positive attitude towards the environment. Therefore, to deal with these issues, it is required an environmental education learning model that can be used as guidelines by teacher. This research used Contextual-Inquiry Based Learning Model that oriented to child's daily environment. Environmental education should be introduced at an early age, so it is very important to implement Contextual-Inquiry Based Learning Model in kindergarten's Environmental Education. In conducting this research, the planning of Environment Education learning using Contextual-Inquiry Based Learning Modelthe implementation of the Environment Education learning using Contextual-Inquiry Based Learning Model the evaluation of Environment Education using Contextual-Inquiry Based Learning Model The method used is descriptive analytical method. The results in this research revealed that the plan developed by teachers in the implementation of Contextual-Inquiry Based Learning Model in teaching environmental education refers to Regulation of Ministry of  National Education No. 58 of 2009 as well as the local content of environmental education. Implementation of learning was conducted through three main stages, namely the introduction, core and closing. While the assessment was carried out using  techniques and procedures to the characteristics of early childhood and learning needs.Keywords: Contextual-Inquiry Based Learning Model, environmental education, early childhood.Abstrak. Penelitian dilatarbelakangi oleh permasalahan lingkungan hidup yang terjadi dewasa ini, yang memerlukan perhatian dari berbagai sektor termasuk sektor pendidikan. Pendidikan lingkungan yang ditanamkan sejak usia dini akan menumbuhkan sikap positif anak terhadap lingkungan hidup. Untuk itu diperlukan sebuah model pembelajaran pendidikan lingkungan hidup yang dapat dijadikan pedoman oleh guru. Model yang dikembangkan adalah Model Pembelajaran Contextual Teaching Learning (CTL) yang berorientasi pada keseharian anak. Mengingat bahwa Pendidikan Lingkungan Hidup sejatinya ditanamkan sejak usia dini, maka sangat penting kiranya untuk mengimplementasikan model pembelajaran CTL dalam pembelajaran Pendidikan Lingkungan Hidup di Taman Kanak Kanak. Secara lebih khusus  perencanaan pembelajaran Pendidikan lingkungan Hidup dengan menggunakan model  pembelajaran Contextual Teaching Learning (CTL) pelaksanaan pembelajaran Pendidikan lingkungan Hidup dengan menggunakan model  pembelajaran Contextual Teaching Learning (CTL)bagaimana penilaian pembelajaran Pendidikan lingkungan Hidup dengan menggunakan model  pembelajaran Contextual Teaching Learning (CTL) Metode penelitian yang digunakan adalah metode deskriptif analitis. Hasil penelitian menunjukan bahwa perencanaan yang dikembangkan oleh guru dalam implementasi model pembelajaran CTL dalam pembelajaran pendidikan lingkungan hidup mengacu pada Permendiknas No 58 tahun 2009 serta Kurikulum Muatan Lokal Pendidikan Lingkungan Hidup. Pelaksanaan ditempuh melalui tiga tahapan utama yaitu pendahuluan, inti dan penutup. Sementara penilaian dilakukan menggunakan teknik dan prosedur yang relevan dengan karakteristik anak usia dini,  serta kebutuhan pembelajaran. Kata Kunci : pembelajaran Contextual Teaching Learning, pendidikan lingkungan hidup, anak usia dini.